Clinical implications of high NQO1 expression in breast cancers - Yang, Yang (BioMed Central, 2014)
BACKGROUND: NAD (P) H: quinone oxidoreductase 1 (NQO1) is a xenobiotic metabolizing enzyme that detoxifies chemical stressors and antioxidants, providing cytoprotection in normal tissues. However, high-level expression of NQO1 has been correlated with numerous human malignancies, suggesting a role in carcinogenesis and tumor progression. This study aimed to explore the clinicopathological significance of NQO1 and as a prognostic determinant in breast cancer. METHODS: A total of 176 breast cancer patients with strict follow-up, 45 ductal carcinoma in situ (DCIS), 22 hyperplasia and 52 adjacent non-tumor breast tissues were selected for immunohistochemical staining of NQO1 protein. Immunofluorescence staining was also performed to detect the subcellular localization of NQO1 protein in MCF-7 breast cancer cells. Eight fresh breast cancers paired with adjacent non-tumor tissues were quantified using real time RT-PCR (qRT-PCR) and western blot. The correlations between NQO1 overexpression and the clinical features of breast cancer were evaluated using chi-square test and Fisher’s exact tests. The survival rate was calculated using the Kaplan–Meier method, and the relationship between prognostic factors and patient survival was also analyzed by the Cox proportional hazards models. RESULTS: NQO1 protein showed a mainly cytoplasmic staining pattern in breast cancer. The strongly positive rate of NQO1 protein was 61.9% (109/176) in breast cancer, and was significantly higher than in DCIS (31.1%, 14/45), hyperplasia tissues (13.6%, 3/22) and adjacent non-tumor tissues (13.5%, 7/52). High-level expression of NQO1 protein was correlated with late clinical stage, poor differentiation, lymph node metastasis, Her2 expression and disease-free and 10-year overall survival rates in breast cancer. Moreover, multivariate analysis suggested that NQO1 emerged as a significant independent prognostic factor along with clinical stage and Her2 expression status in patients with breast cancer. CONCLUSIONS: High-level expression of NQO1 appears to be associated with breast cancer progression, and may be a potential biomarker for poor prognostic evaluation of breast cancers.